Tectonics of the Isua supracrustal belt 1: P-T-X-d constraints of a poly-metamorphic terrane. Garnet, biotite, plagioclase and amphibole chemistry - Ramírez-Salazar, Anthony; Müller, Thomas; Piazolo, Sandra; Webb, A. Alexander; Hauzenberger, Christoph; Zuo, Jiawei; Haproff, Peter; Harvey, Jason; Wong, Tsz Kin; Charlton, Callum (IEDA: EarthChem Library, 2020)
Abstract: EMP data obtained on garnet, biotite, plagioclase and amphibole from rock samples from the Isua supracrustal belt. Samples used for this study were collected in a fieldwork campaign in the Isua supracrustal belt area during the summer of 2017. During this campaign four different sets of samples were collected with different general objectives: “TM” samples were collected for metamorphic studies and make most of the samples used in this study; “JZ” samples were collected for (micro)-structural research, and are the samples used in the companion studied (Zuo et al., submitted); “AW” samples were collected to target the protolith and origin of the ultramafic rocks; and “PH” samples represent some sites in the supracrustal rocks and the tonalites. The four set of samples share rocks collected from the same outcrop such samples share the same name and differ only in the prefixes. For example, samples TM17714-5A and JZ17714-5A were collected from the same lithology and outcrop, with few meters apart, such that they can be considered twin samples.